2022
DOI: 10.1007/s00234-022-03056-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of familial cerebral cavernous malformation syndrome in children: a multicenter cohort study

Abstract: Purpose There is limited data concerning neuroimaging findings and longitudinal evaluation of familial cerebral cavernous malformations (FCCM) in children. Our aim was to study the natural history of pediatric FCCM, with an emphasis on symptomatic hemorrhagic events and associated clinical and imaging risk factors. Methods We retrospectively reviewed all children diagnosed with FCCM in four tertiary pediatric hospitals between January 2010 and March 2022.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Previous studies reported that the seizure outcomes were satisfied in 60%−90% of cases after surgical resection of CCM 13,24 . Resection of hemosiderin rim around the CCM and a shorter duration of seizure symptoms were reported to be associated with favorable seizure control after surgery 13,16,24 . In this study, pure lesionectomy was performed without the removal of a hemosiderin‐stained brain.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Previous studies reported that the seizure outcomes were satisfied in 60%−90% of cases after surgical resection of CCM 13,24 . Resection of hemosiderin rim around the CCM and a shorter duration of seizure symptoms were reported to be associated with favorable seizure control after surgery 13,16,24 . In this study, pure lesionectomy was performed without the removal of a hemosiderin‐stained brain.…”
Section: Discussionmentioning
confidence: 82%
“…Considering the life‐long risk of hemorrhage and the unclear nature of the history of pediatric CCM, studies reporting the long‐term outcomes of pediatric patients managed by radiosurgery and/or conservative treatment with CCM are lacking 6,15,17,21,25 . Several authors have suggested that stereotactic radiosurgery can be administered to adult patients with high surgical risk and prior hemorrhage and can reduce the hemorrhage risk 16 . Other studies demonstrated that Gamma Knife radiosurgery can reduce the hemorrhage risk in pediatric CCM patients and suggested that radiosurgery can serve as a therapeutic alternative for pediatric CCM 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to known statistics, we recommend CM surgical removal in patients with risk factors that increase the possibility of bleeding. These include previous symptomatic bleeding, a positive family history, gender, and age [ 37 , 39 ]. All our operated patients had suffered at least one acute or previous bleeding episode.…”
Section: Discussionmentioning
confidence: 99%